2011
DOI: 10.1371/journal.pone.0021714
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Coupled Theta Activity in Amygdala-Hippocampal-Prefrontal Cortical Circuits during Fear Extinction

Abstract: Signals related to fear memory and extinction are processed within brain pathways involving the lateral amygdala (LA) for formation of aversive stimulus associations, the CA1 area of the hippocampus for context-dependent modulation of these associations, and the infralimbic region of the medial prefrontal cortex (mPFC) for extinction processes. While many studies have addressed the contribution of each of these modules individually, little is known about their interactions and how they function as an integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
239
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(271 citation statements)
references
References 38 publications
(74 reference statements)
21
239
0
2
Order By: Relevance
“…Additionally, correlational analysis of our data revealed that only stressed males showed a significant association between freezing during tone and the metabolic activation of hippocampus, basolateral amygdala and PVN. These results are consistent with previous studies showing a synchronization of the theta frequency range between basolateral amygdala and hippocampus during fear memory retrieval (Seidenbecher, Laxmi, Stork, & Pape, 2003) that declines during extinction learning (Lesting et al, 2011). Indeed, in our case we found a highly significant correlation between the metabolic activation of the hippocampus and the basolateral amygdala during extinction in stressed males and females, but not in the non-stressed groups.…”
Section: Sex-related Differences In Brain Metabolic Activation Duringsupporting
confidence: 93%
“…Additionally, correlational analysis of our data revealed that only stressed males showed a significant association between freezing during tone and the metabolic activation of hippocampus, basolateral amygdala and PVN. These results are consistent with previous studies showing a synchronization of the theta frequency range between basolateral amygdala and hippocampus during fear memory retrieval (Seidenbecher, Laxmi, Stork, & Pape, 2003) that declines during extinction learning (Lesting et al, 2011). Indeed, in our case we found a highly significant correlation between the metabolic activation of the hippocampus and the basolateral amygdala during extinction in stressed males and females, but not in the non-stressed groups.…”
Section: Sex-related Differences In Brain Metabolic Activation Duringsupporting
confidence: 93%
“…Conversely, artificial theta synchronization of LA and HPC during extinction recall (such that PFC firing no longer leads these rhythms) increases freezing to the CS 137 . BLA field potentials and spike activity are entrained to the mPFC theta rhythm during periods of perceived safety (e.g., when mice enter the relative safety of the periphery of the open field 32 ).…”
Section: Synchrony Between Interpretation and Evaluation Circuitsmentioning
confidence: 99%
“…Elevated c-Fos expression in dmPFC and BLA after OF indicated that modifications may involve the dmPFC-BLA Emotional trauma generates silent synapses W Ito et al pathway. Given the dmPFC-BLA interactions are required for PA learning (Malin et al, 2007;Malin and McGaugh, 2006) and correlate with fear memory (Lesting et al, 2011;Popa et al, 2010), the formation of new silent synapses is a potential mechanism to enhance PA learning via strengthening dmPFC-BLA connectivity.…”
Section: Psychological Trauma and Fear Memorymentioning
confidence: 99%
“…Emotionally salient stimuli generally recruit the dorsomedial prefrontal cortex (dmPFC) and the basolateral amygdala (BLA), which have strong reciprocal projections (Hubner et al, 2014;McDonald, 1998) and are involved in fear learning (Gilmartin et al, 2014;Marek et al, 2013;Senn et al, 2014), including contextual learning during observational fear (Amano et al, 2010;Jeon et al, 2010). Fear learning increases oscillatory synchronization between the two structures (Lesting et al, 2011;Likhtik et al, 2014;Stujenske et al, 2014), the amplitude of which correlates with the strength of fear memory (Popa et al, 2010). On the other hand, synaptic inputs from the medial prefrontal cortex to BLA excitatory neurons become attenuated after fear extinction (Cho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%